Evaluation of the Histoplasma capsulatum 100-kilodalton antigen dot blot for the rapid diagnosis of progressive histoplasmosis in HIV/AIDS patients - Rodriguez Laboccetta, Carolina (2023)
Among people living with HIV (PLHIV), progressive disseminated histoplasmosis (PDH) represents an important cause of mortality. Since antigen detection allows a rapid diagnosis and the instauration of a specific treatment this study aimed to evaluate the analytical performance of the Hcp100 dot blot, an in-house assay that detects the Histoplasma capsulatum 100-kilodalton antigen in urine and compare it with 2 commercially available assays the Histoplasma Urine Antigen Lateral Flow Assay (MVD-LFA) (MiraVista® Diagnostics) and the Clarus Histoplasma Galactomannan EIA (Clarus HGM) (IMMY). Urine specimens from 23 PLHIV with PDH, 13 patients with other infectious diseases, and 20 healthy individuals were tested. The Hcp100 dot blot showed higher sensitivity (87.0%), specificity (97.0%) and accuracy (92.9%) than the MVD-LFA (73.9%, 78.8%, and 76.8%, respectively) and the Clarus HGM (78.3%, 90.9%, and 85.7%, respectively). The Hcp100 dot blot had high analytical performance and would be a valuable screening tool for diagnosing PDH among PLHIV.